Fuji apples production capacity under different plant densities, using virus-free scions - Kreuz, Carlos Leomar; Petri, José Luiz; Mondardo, Marcia (Pesquisa Agropecuaria Brasileira, 1996)
The use of production capacity (PC) is a very common practice in apple orchards in the South of Brazil. PC is commonly applied in forecasting yields. In this paper PC is discussed for orchards using virus-free scions in different spacings. The purpose is to help farmers; in their decision of what spacing to use, as well as to evaluate benefits from this technology (virus free scions) on cv. Fuji grafted in MM- 106 XXX, in Santa Catarina State, Brazil. Results show that the most appropriate spacing is 4.5 in between rows and from 1.25 to 1.5 in between plants in the row. Benefits from the use of this technology are, at least, US 2,808.00/ha in adult orchards.